2020
DOI: 10.20885/psikologika.vol25.iss2.art9
|View full text |Cite
|
Sign up to set email alerts
|

Tuntutan Pekerjaan dan Keterikatan Kerja pada Karyawan Bank: Peran Efikasi Diri sebagai Moderator

Abstract: Karyawan yang memiliki keterikatan kerja yang tinggi penting dimiliki oleh perusahaan agar dapat berkompetisi. Penelitian ini bertujuan untuk mengetahui peran efikasi diri sebagai variabel moderator pada hubungan antara tuntutan pekerjaan dan keterikatan kerja. Penelitian ini melibatkan 90 karyawan di Yogyakarta. Skala yang digunakan dalam penelitian ini adalah adaptasi skala The Utrecht Work Engagement Scale (UWES) (Schaufeli & Bakker, 2003), skala Tuntutan Pekerjaan (berdasar Schaufeli & Bakker, 2004), dan s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Researchers from Indonesia also explained that one crucial factor that must be considered when predicting work engagement is the personal element. Some personal variables such as efficacy, optimism, and organization-based self-esteem have been employed in several investigations (Mandala & Nurendra, 2020). Thus, this study aims to investigate the significance of the personal factor influencing work engagement that stems from individual values.…”
Section: A R T I C L E I N F O Abstractmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers from Indonesia also explained that one crucial factor that must be considered when predicting work engagement is the personal element. Some personal variables such as efficacy, optimism, and organization-based self-esteem have been employed in several investigations (Mandala & Nurendra, 2020). Thus, this study aims to investigate the significance of the personal factor influencing work engagement that stems from individual values.…”
Section: A R T I C L E I N F O Abstractmentioning
confidence: 99%
“…Since the Qur'an encourages people to be involved in and committed to their work and forbids unethical behavior and unproductive behavior like begging, laziness, and wasting time, Muslim employees are likely to be satisfied with their jobs and commit to their organization and little or no intention for leaving their organization (Marri et al, 2012). Past research found that permanent staff members at an Islamic institution in Yogyakarta have higher passion and dedication to their work when they adhere to an Islamic work ethic, as they believe that Muslims should be internally motivated to work as hard as they can, due to the belief that their effort is as important as their worship (Mandala & Nurendra, 2020). This is consistent with the idea of work engagement, which holds that motivated workers exhibit vigor, devotion, and absorption, Based on the previous research on how Islamic work ethics influence work engagement, this study advances the previous ones by adding other factors that might influence employees' work engagement in Sharia Bank.…”
Section: A R T I C L E I N F O Abstractmentioning
confidence: 99%
“…Job demands merupakan aspek dari pekerjaan yang berpotensi menyebabkan ketegangan di mana kondisi inI melebihi kemampuan karyawan [12]. Terdapat tiga dimensi dari job demands, yaitu work overload, emotional demands, dan cognitive demands.…”
Section: Frihapma Semita Ade Dkkunclassified